Medical algorithm: Diagnosis and treatment of nonsteroidal antiinflammatory drugs hypersensitivity - Doña, Inmaculada; Pérez-Sánchez, Natalia; Bogas, Gador; Moreno, Esther; Salas, María; Torres-Jaén, María Josefa (Wiley, 2020)
Diagnosis in suspected hypersensitivity reactions to nonsteroidal anti-inflammatory drugs (NSAIDs) is complex as different mechanisms are involved: specific (selective responders, SRs) and nonspecific immunologically mediated (cross-intolerants, CIs)
Keywords: Dermatología; Inmunología; Alergia; Medicina; Nonsteroidal; Antiinflammatory drugs; Allergy; Medical algorithm